1999 Magruder's american government - McClenaghan, William A. (Pearson Prentice Hall U.S.A, 1999)
1999 Prentice Hall Magruder's American Government 1999 Edition (H) by William A. McClenaghan ***ISBN-13: 9780134359854 ***Pages: 798